Impact of Mental Health on Wellness in Adult Workers - Hwang, Won Ju; Jo, Hyun Hee (Frontiers in Public Health, 2021)
Abstract: Wellness in adult workers is intimately associated with better quality of life in individuals, as well as in the family, community, workplace, and country. This study aimed to examine the status of wellness in adult workers and to identify the factors that influence wellness. A descriptive survey was conducted with 260 adult workers. Multiple regression analysis was performed on stress, depression, anxiety, well-being, self-efficacy, and perceived health status. The regression model for wellness in adult workers was significant (F=42.97, P<.001), with an explanatory power of .535. Depression (β=-.315) was identified as the most influential factor for wellness in adult workers, followed by self-efficacy (β=.265) and well-being (β=.263). Depression, stress, and anxiety negatively influenced wellness, whereas self-efficacy, well-being, and perceived health status positively influenced wellness. Study findings suggest the need to develop intervention programs for workers that decrease stress, depression, and anxiety, and incorporate self-efficacy strategies.